2007
DOI: 10.1051/forest:2007032
|View full text |Cite
|
Sign up to set email alerts
|

Morphological evaluation of cork oak (Quercus suber): Mediterranean provenance variability in Tunisia

Abstract: -Twenty-six provenances (2 340 plants) of cork oak (Quercus suber spp.) originating from Portugal, Spain, Italy, Morocco, Algeria, and Tunisia were tested for genetic variation among and within provenances by growth traits. Seven morphometrical characters were measured in 90 plants from each provenance. Analysis of variance showed highly significant differences for all characters. The phenotypic coefficient of differentiation reached 0.24 for the form and 0.22 for height, thus revealing a strong structuring be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 35 publications
6
29
2
Order By: Relevance
“…The species is found in a high variety of climatic conditions: Annual precipitation ranges from 400 to 2000 mm and annual temperatures from 12 to 20°C (Catalan 2003;Alía et al 2009;Aronson et al 2009). Previous studies in common gardens have shown that cork oak populations present high variation in survival, growth, and leaf traits (Gandour et al 2007;Ramirez-Valiente et al 2009a, b;2010;2014a, b, c). Adaptation to contrasting environmental conditions has been suggested as the main mechanism responsible for the differences observed in functional traits among populations (Ramirez-Valiente et al 2009b, 2010, 2014b.…”
Section: Introductionmentioning
confidence: 95%
“…The species is found in a high variety of climatic conditions: Annual precipitation ranges from 400 to 2000 mm and annual temperatures from 12 to 20°C (Catalan 2003;Alía et al 2009;Aronson et al 2009). Previous studies in common gardens have shown that cork oak populations present high variation in survival, growth, and leaf traits (Gandour et al 2007;Ramirez-Valiente et al 2009a, b;2010;2014a, b, c). Adaptation to contrasting environmental conditions has been suggested as the main mechanism responsible for the differences observed in functional traits among populations (Ramirez-Valiente et al 2009b, 2010, 2014b.…”
Section: Introductionmentioning
confidence: 95%
“…Studies on neutral molecular markers have shown a weak effect of neutral evolutionary processes such as genetic drift, founder effects and bottlenecks not derived from strong selection on the population structure of cork oak and few constraints to gene flow among populations (Toumi and Lumaret 1998;Jiménez et al 1999;Ramírez-Valiente et al 2009a). In contrast, significant differences among populations have been reported for a broad set of growth parameters and functional traits (Aranda et al 2005;Gandour et al 2007;Ramírez-Valiente et al 2009a, b) and adaptation to local climate has been viewed as the main factor responsible for such among-population divergence. As a consequence of climate warming, temperatures are expected to increase at least 2^-°C during this century within the cork oak distribution range (IPCC 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although factors affecting seedling survival have been studied in this species, factors affecting other fitness components are currently unknown. Additionally, it is known that cork oak populations differ in survival, growth, and functional traits related to drought stress tolerance (Gandour et al 2007;Ramírez-Valiente et al 2009a;b, 2010a, b), but there is scant knowledge of its intrapopulation genetic diversity, additive genetic variance, and genetic correlations among traits, so the potential for adaptive evolution of the species under a rapidly changing climate remains uncertain.…”
Section: Introductionmentioning
confidence: 99%